2018
DOI: 10.3389/fimmu.2018.02501
|View full text |Cite
|
Sign up to set email alerts
|

Outer-Membrane-Vesicle–Associated O Antigen, a Crucial Component for Protecting Against Bordetella parapertussis Infection

Abstract: Bordetella parapertussis is a respiratory-disease pathogen producing symptomatology similar to that of pertussis but of underestimated incidence and with no specific vaccine existing. We recently designed a vaccine candidate from B. parapertussis outer-membrane vesicles (OMVs) that proved to be safe and protective in a murine-infection model. Based on protection recently reported for the B. parapertussis O antigen in aqueous solution, we assessed here whether the B. parapertussis O-antigen-containing lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…The lipopolysaccharide (LPS)-O antigen was identified as a critical protective antigen of B. parapertussis in a mouse model [ 54 ]. Studies have shown that outer membrane vesicles (OMVs) from B. pertussis , which incorporate the LPS-O antigen from B. parapertussis , effectively protect mice against infections caused by both pathogens [ 55 ]. This approach can significantly expand the effectiveness of pertussis vaccination programs, ensuring comprehensive protection against both pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The lipopolysaccharide (LPS)-O antigen was identified as a critical protective antigen of B. parapertussis in a mouse model [ 54 ]. Studies have shown that outer membrane vesicles (OMVs) from B. pertussis , which incorporate the LPS-O antigen from B. parapertussis , effectively protect mice against infections caused by both pathogens [ 55 ]. This approach can significantly expand the effectiveness of pertussis vaccination programs, ensuring comprehensive protection against both pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This evolution leaves only FHA as an aVP vaccine antigen expressed by Bpp , against which the bactericidal activity of antibodies is weak [49]. Future improved whooping cough vaccines could benefit from comprising Bp-Bpp cross-reacting antigens explicitly, such as the adenylate cyclase [58] or conserved antigens identified through immune-informatics [59], or could incorporate Bpp -specific antigens, such as the O-antigen [60].…”
Section: Discussionmentioning
confidence: 99%
“…This emphasize the synergistic effect of humoral and cellular immunities secreted upon vaccination with the chimeric OMVs-H1/RBD formulation. Serum transfer experiments would be able to further elucidate the role of humoral immunity independent of cellular immunity [49].…”
Section: Discussionmentioning
confidence: 99%